AMORPHOPHALLUS KONJAC AND POLYCYSTIC OVARY SYNDROME (Iraqi Journal of Medical Sciences, 2020)
Background: Polycystic ovary syndrome (PCOS) is that the commonest reproductive endocrine disorder among women of reproductive age, affecting high of population worldwide. It’s the most typical multisystem endocrinopathy having diverse etiopathogenesis in women, causing menstrual irregularities, hirsutism and anovulatory infertility.Objective: To determine the effect of Glucomannan, Amorphophallus konjac supplementation on body weight, body mass index (BMI), Insulin level, insulin resistance indexes, fasting glucose level, luteinizing hormone (LH) level, testosterone, sex hormone binding globulin (SHBG) and lipid profile in over weight and obese women patients with PCOS.Methods: Thirty obese and overweight women with PCOS, mean BMI = 32 kg/m2 with mean age = 29 yr were enrolled in the study. They were received Glucomannan in a dose of 2300 mg daily) for three months. The parameters were measured before and after three months of treatment are BMI, fasting plasma glucose, serum insulin levels, Insulin resistance indexes; homeostasis model assessment of ?-cell function (HOMA-B), homeostasis model assessment of insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI), lipid profile; serum cholesterol, triglycerides, very low density lipoprotein (VLDL-C), low density lipoprotein (LDL-C) and high density lipoprotein (HDL-C), LH, testosterone and SHBG.Results: Glucomannan shows highly significant decrease in weight, glucose, insulin level, HOMAB, HOMAIR, QUICKI, testosterone, LH, serum cholesterol, triglycerides, VLDL-C and LDL-C and highly significant increase in HDL-C and SHBG concentrations, no effect on BMI.Conclusion: Glucomannan was effective in management of patients with PCOS through their ability to decrease the glucose, insulin levels, insulin resistance indexes, lipid profile, testosterone and LH and increase the HDL-C and SHBG.Keywords: PCOS, Glucomannan, obese, overweight, SHBGCitation: Hussein ES, Abu-Raghif AR, Almuaid HA. Amorphophallus konjac and polycystic ovary syndrome. Iraqi JMS. 2020; 18(1): 61-69. doi: 10.22578/IJMS.18.1.9
Keywords: PCOS; Glucomannan; obese; overweight; SHBG